ANALISIS PENERIMAAN PENGGUNA E-RAPOR SMP MENGGUNAKAN EXTENDED TECHNOLOGY ACCEPTANCE MODEL - Gunawan, Gunawan; Zulkarnain, Muhammad Rizki (STMIK Palangkaraya, 2021)
This study aims to analyze the acceptance of junior high school e-Rapor users using Extended Technology Acceptance Model (TAM) by including Subjective Norms factor in the model. The research subjects were 60 e-Rapor users at public junior high school in Banjarmasin. Data collection instrument in the form of questionnaire consisting of 17 points of statement and using 5 point-Likert scale. The research data was analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 3.3.2 software. Based on the results of the study, it is known that Attitude towards Using Technology has a directly significant influence on the Behavioral Intention to use e-Rapor. On the contrary, Subjective Norms do not have a directly significant influence on the Behavioral Intention.